PEMANFAATAN ENERGI PANAS PADA MESIN PENGKONDISIAN UDARA 3/4 PK SEBAGAI MEDIA PEMANAS AIR MANDI - Syadzwina Thasya Noeriska; Muhammad Ridwan Putra; Muchamad Arief Chaeriawan; Muhammad Faisal Saihitua; Rida Zuraida (Jurnal Ilmiah Global Education, 2023)
Air conditioning, commonly known as Air Conditioner (AC) is one type of cooling machine that is widely used by the community, almost in every home and heat energy is wasted in the surrounding environment from outdoor unit devices. The amount of heat energy released to the environment comes from the heat absorbed by the evaporator or indoor unit to the cooled room and added heat energy from the work of the compressor. The heat energy can be reused. The form of utilizing wasted heat energy is to add a pipe from the compressor to the condenser to heat the water. The working process of the AC machine is a closed cycle of the compressor, condenser, capillary tube and evaporator where the cooling medium will work continuously as long as the AC is turned on. Addition of a pipe to heat water for bathing purposes. The test results of the air conditioner using a water heater is an increase in the actual power that is equal to from 1,357 Kw to 1,447 Kw. The heat removed from the condenser decreased from 154.546 kJ/kg to 152.137 kJ/kg. The resulting temperature from a 20 liter water tank is 63.0 OC in 120 minutes.